Statistical Methodologies Symposium celebrating The Work Of Professor Chin-diew Lai - Hong , Choon Ong; Lay , Fong Sin; Li , Ling Tan (2010)
This study briefly look at some of the statistical methods that have been developed to model the HIVIAIDS epidemic and also use the back calculation method to estimate the HIV infection rate in Penang. The back calculation program has been chosen to model the underlying HIVIAIDS epidemic in Penang, Malaysia because it makes use of the AIDS incidence data which is more reflective of the epidemic as compared to the number of HIV infected recorded which is known only if tests are conducted